CALCULATION OF COMPRESSION OF ENTRAPPED AIR AT THE FLOW SEPARATION POINT (European Journal of Interdisciplinary Research and Development, 2026)
A method for determining the parameters of hydraulic shock in a pressure pipeline has been developed, taking into account the compression of air at the point of violation of the integrity of the liquid and the compressed place of formation of discontinuities in the flow continuity. A mathematical model of resource-saving innovative shock-resistant devices for pumping stations of a pressure pipeline and a scientific justification for their parameters have been developed.